SJS-Who? Performance Ethnography and a Practice-Based Pedagogy - Hatton, Oona (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
What is the performative force of practice-based pedagogy? Are there common perceptible outcomes of students engaging in practice-based research (PBR) in a learning environment? This essay utilizes an interview-based performance that is part of a course on performance ethnography to propose three observable features of practice-based pedagogy: intimacy, accountability, and reciprocity. In addition to articulating how PBR aligns with critical performance pedagogy and the performative paradigm, the reflection suggests how one approach to teaching performance ethnography may help to illuminate PBR’s broader methodological contributions.